An Ethnographic Study on Traditional Healing Practices and Their Influence on Medical Treatment Adherence - Prita Rahajeningtyas Kusuma Wardani, Nimas; Fitrahulil Jannah, Insani; Tunggal, Deif; Syahrir (Golden Ratio of Data in Summary, 2025)
This study explores the intersection between traditional healing practices and medical treatment adherence through a qualitative literature-based analysis grounded in an integrative ethnographic framework. The objective is to examine how cultural beliefs, spiritual interpretations of illness, and healer-patient dynamics influence adherence behaviors, particularly within low- and middle-income contexts where medical pluralism is prevalent. The research adopts a constructivist epistemology, employing a systematic review of 37 peer-reviewed qualitative and mixed-methods studies published between 2015 and 2025. Data were thematically synthesized to identify key patterns in dual treatment use, cultural logics of illness, relational trust, and healthcare system interfaces. The findings reveal that traditional healing does not inherently contradict biomedical adherence but interacts with it in complex and context-dependent ways. Patients often navigate between healing systems based on cultural alignment, familial influence, and perceived trustworthiness, while systemic barriers such as inadequate communication and institutional mistrust further complicate adherence. Integrative models—such as healer-clinic collaborations, culturally tailored counseling, and participatory communication strategies—demonstrated improved adherence outcomes in several settings. The study contributes to theoretical frameworks of adherence by incorporating sociocultural dimensions and proposes managerial innovations to institutionalize culturally embedded practices. It concludes by emphasizing the need for sustainable, inclusive health models that bridge epistemic divides between biomedicine and indigenous knowledge systems. These findings offer implications for health system reform, policy integration, and community-based intervention design in pluralistic healthcare environments.